Life, death and coming of age in antiquity (Leiden)
xiii, 552 sayfa
Keywords: “Biological and social life of human beings is punctuated by rites of passage. Although some of them are documented in detail, rites of passage in ancient Near Eastern cultures have not previously been presented comprehensively and parallel to each other. A thorough study is achieved in this volume by combining various approaches and disciplines. The basic rites of passage are examined: birth, adolescence, changes of social status, and death. The present volume consists of twenty-one contributions by specialists of ancient Mesopotamia, Anatolia, Egypt, and neighbouring cultures. It is structured around three main axes: “Becoming someone: The social dimension of rites of passage, ' where the interface between the religious sphere and the socio-political structure is examined; 'Real life, symbolic life: Ritualized life and death in rites of passage, ' or how each threshold crossed by an individual is perceived as a new beginning; and 'Liminality and impurity: The dangers of transformation, ' which defines the complex relation between notions of purity and impurity and rites of passage.” --